Big Repair Project: using citizen science to better understand the factors affecting household maintenance and repair of home appliances and electronics across the UK - Pencheva, Polina; Purkiss, Danielle; Hewlett, Robert; Miodownik, Mark (Frontiers in Sustainability, 2025)
The world is facing an increasing challenge with the accumulation of Waste Electrical and Electronic Equipment leading to a wide range of negative environmental and social impacts. Supporting higher priority circular economy activities such as repair and extending the lifespan of electrical and electronic equipment (EEE) will help to reduce WEEE's negative impacts, create skilled jobs, and improve supply chain resilience. This requires citizens to be able to identify EEE products as repairable, have basic repair skills, access to repair services (including diagnostics) and motivation to repair. Using a citizen science approach over a 32-month period from January 2022 to September 2024, the Big Repair Project collected 5,958 survey responses and 473 detailed logs of repair activities from people geographically spread across the UK. The data was analyzed to better understand issues that currently exists with household maintenance and repair of home appliances and electronics. Findings reveal a gap between consumer expectations of product lifespan and existing legislation, challenges related to cost and accessibility of repair services, and a desire for improved repair information and spare parts availability. The findings emphasize the need for policy and industry action to diversify local repair economies, extending statutory warranty periods, support diagnostics and repair transparency, and incentivize repair businesses. By fostering a culture of repair, this work aims to inform the development of UK Right to Repair laws and broader circular economy initiatives, contributing to the reduction of electronic waste and the promotion of sustainable consumption practices.